New experimental data on the human dermal absorption of Simazine and Carbendazim help to refine the assessment of human exposure - Bányiová, Katarína; Nečasová, Anežka; Kohoutek, Jiří; Justan, Ivan; Čupr, Pavel (Chemosphere, 2016)
Due to their widespread usage, people are exposed to pesticides on a daily basis. Although these compounds may have adverse effects on their health, there is a gap in the data and the methodology needed to reliably quantify the risks of non-occupational human dermal exposure to pesticides. We used Franz cells and human skin in order to measure the dermal absorption kinetics (steady-state flux, lag time and permeability coefficient) of Carbendazim and Simazine. These parameters were then used to refine the dermal exposure model and a probabilistic simulation was used to quantify risks resulting from exposure to pesticide-polluted waters. The experimentally derived permeability coefficient was 0.0034 cm h(-1) for Carbendazim and 0.0047 cm h(-1) for Simazine. Two scenarios (varying exposure duration and concentration, i.e. environmentally relevant and maximum solubility) were used to quantify the human health risks (hazard quotients) for Carbendazim and Simazine. While no risks were determined in the case of either scenario, the permeability coefficient, which is concentration independent and donor, formulation, compound and membrane specific, may be used in other scenarios and exposure models to quantify more precisely the dermally absorbed dose during exposure to polluted water. To the best of our knowledge, the dermal absorption kinetics parameters defined here are being published for the first time. The usage of experimental permeability parameters in combination with probabilistic risk assessment thus provides a new tool for quantifying the risks of human dermal exposure to pesticides.
Keywords: techniky in vitro; pesticidy; Humans; lidé středního věku; permeabilita; kožní absorpce; Permeability; Benzimidazoles; Female; Models, Biological; kůže; dospělí; Simazine; lidé; Carbendazim; Permeability coefficient; Human dermal absorption; benzimidazoly; Pesticides; Probabilistic risk assessment; Adult; Kinetics; ženské pohlaví; Male; Middle Aged; simazin; Skin Absorption; biologické modely; In Vitro Techniques; Carbamates; karbamáty; Risk Assessment; mužské pohlaví; hodnocení rizik; kinetika; Skin